Cohort Profile: Tracing Achievements, Key processes and Efforts in professional care for Children and Adolescents REsearch; TAKECARE. (18th December 2014) - Verhage, Vera; Noordik, Erik; Knorth, Erik J; Reijneveld, Sijmen A
Abstract: TAKECARE is a prospective cohort study designed in The Netherlands to obtain evidence on the care chain for children and adolescents with psychosocial problems, and its long-term outcomes. Little is known about the content of care as offered and on whether the care is adequate. The cohort consists of children and adolescents entering care for psychosocial problems (care sample, n = 1382) and a random sample of the general population (community sample, n = 666). Children were eligible for participation if they were aged 4–18 years (inclusive) and had estimated IQs of 70 and over. The care sample covers the fields of Preventive Child Healthcare (PCH), Child and Adolescent Social Care (CASC) and Child and Adolescent Mental Healthcare (CAMH). Children, parents or guardians and involved practitioners completed five questionnaires (baseline, and at 3, 12, 24 and 36 months thereafter). The main categories of data concern the sociodemographic characteristics of children and their parents or guardians, the characteristics of entry into care and care content, and intermediate and final treatment outcomes. Information about data access can be requested by e-mail: c4youth@umcg.nl .